2022
DOI: 10.15376/biores.17.3.5129-5145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preservative treatment on physical and mechanical properties of bamboo (Gigantochloa scortechinii) strips

Abstract: Using a vacuum pressure cylinder, Gigantochloa scortechinii was treated with boron and copper chrome boron (CCB) preservative at different concentrations of 2% and 3%. The treatability of untreated and treated bamboo, as well as its physical and mechanical properties, were investigated. Both preservatives showed a high level of penetration into the bamboo strips. Weight percent gain (WPG) and extent of retention of CCB-treated bamboo strips were higher than those of the boron-treated samples. Swelling and shri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Compared to boron treatment, using copper chrome boron (CCB) preservatives resulted in a higher Modulus of Rupture (MoR) and CS for the treated bamboo. This indicates a positive influence on the suitability of bamboo, especially in structural applications [14]. Scanning electron microscopy (SEM)-energy dispersive X-ray (EDX) analysis revealed that an increase in bamboo fiber content without a corresponding increase in natural rubber latex content resulted in the formation of void spaces within the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to boron treatment, using copper chrome boron (CCB) preservatives resulted in a higher Modulus of Rupture (MoR) and CS for the treated bamboo. This indicates a positive influence on the suitability of bamboo, especially in structural applications [14]. Scanning electron microscopy (SEM)-energy dispersive X-ray (EDX) analysis revealed that an increase in bamboo fiber content without a corresponding increase in natural rubber latex content resulted in the formation of void spaces within the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the years, wood preservatives such as those with arsenic and chromium content have been banned due to their harm caused to the environment and the users (Baharuddin et al, 2022;Ibáñez et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The cavities in the bamboo trunk separated by membranes and called nodes. The internode length of bamboo varies, and the intermediate internodes are longer than the base and shoot apex, as in [1], [2], [3], [4], and [5]. Fasteners transmit shear forces and prevent or reduce movement between bamboo and concrete panels.…”
Section: Introductionmentioning
confidence: 99%